2022
DOI: 10.3389/fpubh.2022.1066899
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution exposure and pregnancy outcomes among women with polycystic ovary syndrome

Abstract: BackgroundRecently, the relationship between air pollution and reproductive outcomes has become a research focus. However, there is a lack of research on the relationship between air pollution and polycystic ovary syndrome (PCOS).MethodsThis is a retrospective cohort study included a total of 1,652 women with PCOS and 12,543 women without PCOS conducted from 1 January 2015 to 31 December 2019. The average daily concentration data of six air pollutants (PM2.5, PM10, O3, NO2, SO2, and CO) during different exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Air pollution is an increasing global problem that has been associated with a wide variety of human diseases, including PCOS (5,(29)(30)(31)(48)(49)(50). Air polution consists of a range of components including gases (SO2, NOx, NO, NO2) and suspended particulates of different sizes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Air pollution is an increasing global problem that has been associated with a wide variety of human diseases, including PCOS (5,(29)(30)(31)(48)(49)(50). Air polution consists of a range of components including gases (SO2, NOx, NO, NO2) and suspended particulates of different sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Microparticulate air pollution is believed to account for a large proportion of the public health impact of air pollution, including reproductive diseases (50,52). MAP has been associated with menstrual irregularity (53), infertility (25,30), adverse pregnancy outcomes (31), increased incidence of PCOS (5,29), and has also been linked to transgenerational transmission and infant weight gain (54,55). Human studies have shown that metabolites of tobacco (cadmium, cotine) can be found in ovarian follicular fluid and may potentially affect the developing egg (42,53).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations